Women, Gender and Development in the Caribbean. Reflections and Projections - Bodil Folke Frederiksen (The Royal Danish Library, 2003)
Bodil Folke Frederiksen anmelder "Women, Gender and Development in the Caribbean. Reflections and Projections" af Patricia Ellis.